Bio-Precipitation of Calcium Ions Induced by Free and Immobilized Virgibacillus dokdonensis WLR1 in Hypersaline Wastewater. Issue 8 (1st August 2022) - Yan, Huaxiao; Wei, Lirong; Han, Zuozhen; Tucker, Maurice E.; Zhao, Yanhong; Meng, Long; Zhao, Lanmei; Wang, Jihan; Xu, Yudong; Geng, Heding; Zhang, Xiyu; Qiu, Ziyang; et al.
Abstract: Hypersaline wastewater has been widely used in industrial processes in some countries short of freshwater, but calcium ions in such wastewater should be removed due to the danger of limescale being produced. In this study, calcium ions in hypersaline (sodium chloride: 5%) wastewater was biomineralized into different carbonate minerals under the action of free and immobilized Virgibacillus dokdonensis WLR1 bacteria. The results show that the calcium ion precipitation rate was much higher under the conditions of immobilized bacteria ( p  < 0.01), and that there was a significant difference in the mineral phases, the diversity of protein secondary structures and morphologies, and chemical characteristics of the mineral surfaces between the free and the immobilized bacteria based on XRD, FTIR, SEM-EDS, and XPS analyses. TG, DTG, and DSC results show that with increasing calcium ion concentrations, the thermal stability of calcium carbonate under the conditions of free bacteria decreased due to the decline in crystallinity. The stable carbon isotope values (δ 13 CPDB ) of calcium carbonate formed by free bacteria changed from −16.80‰ to −18.17‰; the much more negative δ 13 CPDB values suggest that the calcium carbonate minerals are biotic. From ultrathin slices analyzed by HRTEM-mapping-SAED, it was observed that calcite is formed inside the cell, thus also facilitating calcium ion removal. Research concerning intracellular calcite has rarely been reported. This study helps to further understand the mechanisms of biomineralization, and also provides an environmentally friendly method to remove calcium ions from hypersaline wastewater.